Genetic Analysis Using a Next Generation Sequencing-Based Gene Panel in Patients With Skeletal Dysplasia: A Single-Center Experience - Kim, Su Jin; Lee, Sae-Mi; Choi, Jong-Moon; Jang, Ja-Hyun; Kim, Hyun Gi; Kim, Jung-Taek; Cho, Jae Ho; Sohn, Young Bae (Frontiers in Genetics, 2021)
Skeletal dysplasia (SD), a heterogeneous disease group with rare incidence and various clinical manifestations, is associated with multiple causative genes. For clinicians, accurate diagnosis of SD is clinically and genetically difficult. The development of next-generation sequencing (NGS) has substantially aided in the genetic diagnosis of SD. In this study, we conducted targeted NGS of 437 genes—included in the nosology of SD published in 2019—in 31 patients with suspected SD. The clinical and genetic diagnoses were confirmed in 16 out of the 31 patients, and the diagnostic yield was 51.9%. In these patients, 18 pathological variants were found in 13 genes (COL2A1, MYH3, COMP, MATN3, CTSK, EBP, CLCN7, COL1A2, EXT1, TGFBR1, SMAD3, FIG4, and ARID1B), of which four were novel variants. The diagnosis rate was very high in patients with suspected familial SD and with radiological evidence indicating clinical SD (11 out of 15, 73.3%). In patients with skeletal involvement and other clinical manifestations including dysmorphism or multiple congenital anomalies, and various degrees of developmental delay/intellectual disability, the diagnosis rate was low (5 out of 16, 31.2%) but rare syndromic SD could be diagnosed. In conclusion, NGS-based gene panel sequencing can be helpful in diagnosing SD which has clinical and genetic heterogeneity. To increase the diagnostic yield of suspected SD patients, it is important to categorize patients based on the clinical features, family history, and radiographic evidence.